USING TALK SHOW TECHNIQUE VIEWED FROM STUDENTS’ PERSONALITY ON STUDENTS’ SPEAKING SKILL - Nur Hasnani Putri Akhmad Jaeni; Yunik Susanti; Diani Nurhajati (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
This research aims to investigate the impact of role-playing techniques with talk shows viewed from student personality (introvert-extrovert) for the senior high school students. One group pre-test and post-test design was used in this study by using speaking performance test to collect the data. The collected data then analyzed using t-test computation. The results of the data analysis showed that there are more introverted students than extroverted students. After the implementation of role play with talk show the students' speaking skills increased, with the scores of the introverted students were higher than those of the extrovert students. The t-test computation showed that there is significant effect of using role play with talk show to the students’ speaking ability viewed from their personality. It can be concluded that role play with talk show is suitable to teach speaking and it is suggested that the teacher should apply this technique and pay attention on identifying the students’ personality before teaching.